THE ROLE OF PUBLIC RELATIONS IN IMPROVING A POSITIVE IMAGE IN THE COMPANY PT. SORIK MARAPI GEOTHERMAL POWER (SMGP) MANDAILING NATAL DISTRICT - Elviana Elviana; Muhammad Alfikri (KABILAH : Journal of Social Community, 2022)
Abstract: This study aims to determine the role of public relations in increasing the positive image of PT. Sorik Marapi Geothermal Power (SMGP) Mandailing Natal District. The method used in this research is a descriptive qualitative method. Primary data sources, the authors obtain data through observation, interviews, and documentation of affected parties, especially the Public Relations company PT. Sorik Marapi Geothermal Power Plant (SMGP) located in Mandailing Natal Regency and secondary data comes from books, journals, articles, internet and e-books. Data analysis techniques by means of this research data will be analyzed from the start. The data is then reprinted, systematized, and logically evaluated to obtain valid and credible data. The results of the study show that the role of public relations for PT SMGP in the Mandailing Natal among others, is as an expert advisor as a communication facilitator and as a problem solving facilitator. Keywords: The Role of Public Relations, Positive Company Image